1995
DOI: 10.1210/jcem.80.6.7775647
|View full text |Cite
|
Sign up to set email alerts
|

Human chorionic gonadotropin-dependent expression of vascular endothelial growth factor/vascular permeability factor in human granulosa cells: importance in ovarian hyperstimulation syndrome.

Abstract: Ovarian hyperstimulation syndrome (OHSS) is a severe complication arising from controlled ovarian stimulation treatment. This iatrogenic condition is potentially lethal and occurs in 0.3-5% of stimulated ovarian cycles. hCG exacerbates OHSS. The pathophysiology of OHSS is still unknown; therefore, treatment regimens are aimed at ameliorating symptoms. Prominent features of OHSS are an elevated risk of thromboembolism due to enhanced production of von Willebrand factor by endothelial cells and ascites, or pulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1
7

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(52 citation statements)
references
References 14 publications
3
40
1
7
Order By: Relevance
“…In addition to endothelial cells, VEGF gene and protein are also expressed in ovarian granulosa cells, granulosa-lutein cells, thecal cells and thecal-lutein cells [4-6]. It has been found that changes in VEGF expression and its distribution in the ovary are closely related to follicular development and ovulation [7-9]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition to endothelial cells, VEGF gene and protein are also expressed in ovarian granulosa cells, granulosa-lutein cells, thecal cells and thecal-lutein cells [4-6]. It has been found that changes in VEGF expression and its distribution in the ovary are closely related to follicular development and ovulation [7-9]. …”
Section: Introductionmentioning
confidence: 99%
“…In cultured bovine ovarian granulosa cells (GC), either LH or E2 can stimulate VEGF mRNA expression, but the effects of LH are more rapid (48). Cultured human GC respond to hCG with increased VEGF mRNA production (49); this leads us to speculate that in our patients there is a sequential action of the administered hormones (FSH, human menopausal gonadotropins, and hCG) to first directly stimulate VEGF production. This is followed by increased estrogen production that independently augments VEGF.…”
Section: Discussionmentioning
confidence: 91%
“…VEGF-A increases capillary permeability and promotes angiogenesis (Geva & Jaffe, 2000). HCG stimulates VEGF production in human granulosa cells and increases serum VEGF levels (Neulen et al, 1995;Pellicer et al, 1999). Serum VEGF levels were found to be higher in women during the course of OHSS compared to a control group without OHSS (Abramov et al, 1997).…”
Section: Human Fertilitymentioning
confidence: 91%